2017
DOI: 10.1177/0165025416687412
|View full text |Cite
|
Sign up to set email alerts
|

The development of emotional and behavioral self-regulation and their effects on academic achievement in childhood

Abstract: Self-regulation is an essential ability of children to cope with various developmental challenges. This study examines the developmental interplay between emotional and behavioral self-regulation during childhood and the relationship with academic achievement using data from the longitudinal Millennium Cohort Study (UK). Using cross-lagged panel analyses, we found that emotional and behavioral self-regulation were separate and stable constructs. In addition, both emotional and behavioral self-regulation had po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 63 publications
3
56
1
4
Order By: Relevance
“…Furthermore, it was also found that intellectual functioning was negatively correlated to the degree of understanding of emotions (Cook, Greenberg, & Kusche, 1994). Although the relationship between the ability to regulate behaviour and emotions in social situations and the school achievement was not found in our research, it was found in the study conducted by Edossa, Schroeders, Weinert and Artelt (2018). Specifically, it was determined that emotional and behavioural self- Furthermore, no significant correlation was found between the overall social and emotional competence (Strength Index) and school success in any class, meaning that the hypothesis number two (H2) of this study was not confirmed.…”
Section: The Relationship Between School Success and The Development contrasting
confidence: 57%
“…Furthermore, it was also found that intellectual functioning was negatively correlated to the degree of understanding of emotions (Cook, Greenberg, & Kusche, 1994). Although the relationship between the ability to regulate behaviour and emotions in social situations and the school achievement was not found in our research, it was found in the study conducted by Edossa, Schroeders, Weinert and Artelt (2018). Specifically, it was determined that emotional and behavioural self- Furthermore, no significant correlation was found between the overall social and emotional competence (Strength Index) and school success in any class, meaning that the hypothesis number two (H2) of this study was not confirmed.…”
Section: The Relationship Between School Success and The Development contrasting
confidence: 57%
“…Confirmatory for factor analyses for the MTAS were checked for the sub-sample in order to check measurement properties at test and re-test. Temporal invariance was then checked by conducting a series of models with increasingly stringent constraints (Edossa, Schroeders, Weinert, & Artelt, 2018). The configural invariance model specifies the MTAS at both measurement points, the threshold invariance model constraints item loadings and thresholds to be invariant, and the error invariance model constraints item residual variances to be invariant.…”
Section: Participantsmentioning
confidence: 99%
“…Several studies focus mainly on the relationship between academic self-efficacy, motivation to mastery and performance goals, on emotional intelligence and motivation to learn (Gharetepeh, Safari, Pashaei, Razaei, & Kajbaf, 2015;Rowe, Fitness, & Wood, 2015;Umaru & Umma, 2015;Edossa, Schroeders, Weinert, & Artelt, 2018;Somayyeh, Manizheh, & Manouchehr, 2018). Few studies focus instead on emotional self-efficacy in the self-regulation of positive and negative emotions and achievement motivation in university students.…”
Section: Connection Between Emotional Self-efficacy and Motivational mentioning
confidence: 99%